The Level of Depression in Third Trimester Pregnancy, With and Without Anemia - Primada, Lyla Fitrania; Wardani, Natalia Dewi; Pramono, M. Besari Adi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Anemia is a health problem worldwide, especially in pregnancy, as it can cause depression. Antenatal depression can cause impaired fetal growth and development, bleeding and abortion, prematurity, low birth weight babies, and postpartum depression. This research aims to determine the difference in levels of depression between anemia and non-anemia in the third trimester of pregnancy. It is an observational study with a cross-sectional design. The samples were 75 last-trimester pregnant women who did antenatal care in Diponegoro National and Amino Gondohutomo Hospital, and also Halmahera and Ngesrep Health Center in Semarang and willling to be respondents selected using a purposive sampling method. Data collection used a validated Edinburgh Postnatal Depression Scale (EPDS) questionnaire with a Content Validity Index (CVI) of 1.00 and a reliability of 0.706. Mann Whitney and Kruskal Wallis were utilized to analyze data. There were 38 respondents with anemia and 37 respondents without anemia. The 12 respondents (31.6%) with anemia had a risk of depression, and 13 respondents (35.1%) without anemia had a risk of depression. There was no significant difference in the level of depression in the third trimester of pregnancy with and without anemia (P0,05).